2018
DOI: 10.1111/jam.14150
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium on oxidative damage and antioxidant enzymes of eukaryotic cells: wine Saccharomyces cerevisiae

Abstract: Aim: To clarify the effects of selenium (Se), parameters related to oxidative issues, as well as the antioxidant response were investigated on an autochthonous wine yeast strain. Methods and Results: Antioxidant enzyme activity, gel electrophoresis, Western blot and MDA level were used to investigate the effects of different concentration of Se in wine yeast. We found that Se is able to affect the enzymatic activities of catalase (CAT), glutathione peroxidase (GPx) and superoxide dismutase (SOD). An increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…SelP is the first protein discovered to contain more than one Se atom in the form of SeCys. It has also been shown that Pselenoprotein protects lipoproteins against oxidation by removing the peroxynitrite molecule that is formed due to oxidative stress within cells as a result of the reaction between superoxide ions with nitric oxide molecules at sites of inflammation [17][18][19]. The assumption that SelP is secreted into the bloodstream, as well as several SeCys sequences that are found in its structure, indicates that SePs can become a source of Se for peripheral tissues [20,21].…”
Section: Selenoprotein-p (Selp)mentioning
confidence: 99%
“…SelP is the first protein discovered to contain more than one Se atom in the form of SeCys. It has also been shown that Pselenoprotein protects lipoproteins against oxidation by removing the peroxynitrite molecule that is formed due to oxidative stress within cells as a result of the reaction between superoxide ions with nitric oxide molecules at sites of inflammation [17][18][19]. The assumption that SelP is secreted into the bloodstream, as well as several SeCys sequences that are found in its structure, indicates that SePs can become a source of Se for peripheral tissues [20,21].…”
Section: Selenoprotein-p (Selp)mentioning
confidence: 99%
“…This system consists of an enzymatic antioxidant system formed by the studied enzymes SOD, catalase and GPx and an extensive non-enzymatic or chemical antioxidant system that the analyzed vitamin C is part of. 74,75 The effectiveness of these three enzymes is due to a triple defensive action: they reduce ROS and they prevent the interaction of ROS to give rise to species of higher reactivity and finally they repair oxidized macromolecules. In the absence of oxidative stress, generated ROS are held to very low levels due to the coordinated action of these enzyme systems.…”
Section: Oxygenic Metabolism Evolution Of Sod Cat and Gpxmentioning
confidence: 99%
“…Role of selenium in human body is important and crucial in stabilising and neutralising the body metabolism. During wound healing process, certain selenoproteins like GPX-1, GPX-4, selenoprotein S and selenoprotein P combine to perform various reactions such as antioxidant activities, inhibition of inflammatory cytokines and elimination of Peroxynitrate (a super radical ion) in inflammatory phase (Lei et al 2009;Cox et al 2013;Talbi et al 2019).…”
Section: Introductionmentioning
confidence: 99%